MAGANG KEWIRAUSAHAAN FINISHING KERAMIK BAGI MAHASISWA PROGRAM STUDI PENDIDIKAN SENI KERAJINAN - Dewojati, Darumoyo (Universitas Negeri Yogyakarta, 2010)
This program is aimed at giving sufficient practical experience in the form of knowledge, skills, and motivation and attitude appreciation, to the targeted students objectively, in connection with the entire practical works in a ceramic industry. This program is intended to internalize enterpreneurship values and spirit, that will have significant roles in preparing students facing the challenge dan jiwa enterpreneurship, that will provide significant practical experience to them in facing the challenge of finding suitable works after their graduation. The program involves 10 students of Craft Education Study Program, Faculty of Languages and Arts, Yogyakarta State University, and a finishing ceramic industry, i.e., Tunas Asri Keramik Yogyakarta, as a patner. The main methods and implementation of the program are conducted through lecturing and discussing, for the preparatory stage to give sufficient knowledge to the tagetted students, followed by the practical method as the implementation stage of the program by which the students are given the change to participatively involved in the industry. The latter method is conducted for 15 days with 8 hours effective working hours everyday. The result of the implementation of the program can be summarized as follows. Firstly, all the participants have actively involved in the entire program activities, namely, a) the preparatory lecturing on enterpreneurship topic in campus, b) learning and having practical activity of finishing ceramic prodct throuh various tecniques, c) learning the industrial management, and d) learning to write a proposal of establishing a new finishing ceramic industry. Secondly, all of the targeted students finish writing the proposal of establishing a new industry. This program is beneficial in giving practical experience to the students, consequently, this program should be continously developed and improved in the future.